Antibacterial Activity of Lactobacillus Casei on Some Pathogenic Bacteria - Hamza, Zaman S.; Al-Ajeeli, Zahraa A. (International Journal of Scientific Research in Biological Sciences, 2023)
Well-known probiotic L. casei has positive benefits on human health. Finding L. casei`s antimicrobial capabilities was the goal of this investigation. L. Casei was acquired from the Microbiology Department at Babylon University`s Science College. With the use of well diffusion agar procedures, the antimicrobial properties regarding such bacterial culture supernatants have been examined against four pathogenic bacterial strains (E. coli, S. aureus, S. pyogen, and K. pneumoniae) at varied concentrations (50,100,150,200 ?L). In this investigation, it was found that raising the concentration of Culture supernatants in a well also increased the growth inhibition. The results showed that 200 ?L higher concentrations of L. casei supernata fully prevented the growth of all of such bacteria while 50 ?L lower concentrations only had a minimal effect. Additionally, these results demonstrate that, while K. pneumonia has a modest inhibition zone at the same dose, E. coli has a 200 ?L higher inhibition efficiency than other bacteria.